(untitled) (Лучшие интеллектуальные исследования, 2025)
Annotation. This article discusses about useful, non-traditional methods and techniques of language learning and their practical significance. In addition, a description of each method and techniques is provided for learning and teaching some significant aspects of languages. The main purpose of using such kind methods in the field of language learning is to arise students’ interest in language skills, to increase their knowledge of the language and use of important aspects of language. This allows you to add a variety of innovations and effective styles to the language. Also, the use of such methods at lessons not only helps to enrich the knowledge of the person, but also to increase his interest. The next advantage of these approaches is that to expand the scientific worldview.